Gliotoxin from Aspergillus fumigatus Abrogates Leukotriene B4 Formation through Inhibition of Leukotriene A4 Hydrolase. Issue 4 (18th April 2019) - König, Stefanie; Pace, Simona; Pein, Helmut; Heinekamp, Thorsten; Kramer, Jan; Romp, Erik; Straßburger, Maria; Troisi, Fabiana; Proschak, Anna; Dworschak, Jan; Scherlach, Kirstin; Rossi, Antonietta; et al.
Summary: The epidithiodioxopiperazine gliotoxin is a virulence factor of Aspergillus fumigatus, the most important airborne fungal pathogen of humans. Gliotoxin suppresses innate immunity in invasive aspergillosis, particularly by compromising neutrophils, but the underlying molecular mechanisms remain elusive. Neutrophils are the first responders among innate immune cells recruited to sites of infection by the chemoattractant leukotriene (LT)B4 that is biosynthesized by 5-lipoxygenase and LTA4 hydrolase (LTA4 H). Here, we identified gliotoxin as inhibitor of LTA4 H that selectively abrogates LTB4 formation in human leukocytes and in distinct animal models. Gliotoxin failed to inhibit the formation of other eicosanoids and the aminopeptidase activity of the bifunctional LTA4 H. Suppression of LTB4 formation by gliotoxin required the cellular environment and/or reducing conditions, and only the reduced form of gliotoxin inhibited LTA4 H activity. Conclusively, gliotoxin suppresses the biosynthesis of the potent neutrophil chemoattractant LTB4 by direct interference with LTA4 H thereby impairing neutrophil functions in invasive aspergillosis. Graphical Abstract: Highlights: Gliotoxin suppresses neutrophil influx and LTB4 formation in mice and rats Gliotoxin selectively inhibits LTB4 biosynthesis via inhibition of LTA4 H Gliotoxin blocks epoxide hydrolase but not aminopeptidase activity of LTA4 H Reducing conditions confer gliotoxin LTA4 H inhibitory activity Abstract : König et al. identified leukotriene A4 hydrolase (LTA4 H) in human leukocytes as a molecular target of gliotoxin from Aspergillus fumigatus. Under reducing conditions, gliotoxin inhibits leukotriene A4 hydrolase activity leading to suppression of chemotactic leukotriene B4 biosynthesis and neutrophil infiltration, which may underlie the neutrophil-compromising properties of this fungal toxin.